Hemotropic Mycoplasma ovis infection rate among goats in Ladang Angkat, Faculty of Veterinary Medicine, Universiti Putra Malaysia - Abu Jazid, Nurul Hafizah (2015)
Hemotropic Mycoplasmosis infects sheep and goats worldwide, which also lead to economic losses. For Malaysia, there is still lack of information documented for Mycoplasma ovis infection among goats. In this study, 10 goats from five Ladang Angkat, Faculty of Veterinary Medicine (FVM) were sampled, M. ovis infection and intestinal parasites burden was determined using Giemsa stain and Modified McMaster technique respectively. Fly trap was used to trap biting fly and questionnaire was given to each farm. All the data were statistically analysed. Out of 50 samples, 47 samples (94.0%) were positive with M. ovis infection. Among the positive samples, 44 samples (93.6%) were mild infection and three samples (6.4%) were moderate infection with highest infection rate of 38.5% parasitemia. No biting fly was trapped; questionnaire revealed that all farms located in endemic area, and presence of carrier animals. Statistically, there were no significant difference in egg per gram (e.p.g) and oocyst per gram (o.p.g) with level of parasitemia, and there were no significant correlation between infection rate of M. ovis with e.p.g and o.p.g. As conclusion, occurence rate of M. ovis is high among Ladang Angkat FVM but the parasitemia levels were generally mild.